PROXIMAL ARTERIO VENOUS FISTULA CREATION - A GOLD STANDARD IN CHRONIC RENAL FAILURE PATIENTS WITH MULTIPLE COMORBIDS - Jamil, Muhammad; Usman, Rashid; Ali, Kishwar (Journal of Ayub Medical College Abbottabad, 2018)
Background: Patients with end stage renal disease need an accurate and effective vascular access for haemodialysis. This study was conducted to postulate a hypothesis that proximal arterio venous fistula (AVF) creation should be a gold standard in Chronic Renal Failure (CRF) patients with multiple co morbidities. Methods: A total of 230 patients reporting to Vascular Surgery Clinic in Combined Military Hospital Lahore and Peshawar from January 2014 to January 2016 for AVF creation, were included and equally divided into two groups by random draw method. Distal AVF created in Group A and proximal AVFs at elbow in Group B. The data regarding age, gender, atherosclerotic risk factors, body mass index (BMI) was recorded. The groups were compared for functional maturation of AVF and their patency at 6 and 12 months. Results: Mean age was 30±SD 6.5 years (31±SD 5.1 in Group A, 30±SD 6.9 in Group B) with a male to female ratio of 5.4:1. In terms of age (p-value 0.529), gender (p-value 0.716), diabetes (p-value 0.682), hypertension (p-value 0.659) and BMI; there was no difference between two groups. 85.2% (n=98) AVFs matured in Group B as compared to 44.3% (n=51) AVFs in Group A (p-value=0.0045). Furthermore, statistically significant differences between the two groups were found in terms of patency rates at 6 and 12 months (73.9% and 66% in Group B: 26.9% and 16.5% in Group A; p-value 0.0039 and 0.0007 respectively). Conclusion: Proximal AVF creation in CRF patients with multiple co morbidities should be the gold standard as a primary procedure in terms of better long term primary patency. Keywords: co morbidity; creation; Aold standard; proximal AVF